Pogląd Kazimierza Twardowskiego na temat zajmowania się przez filozofię „poglądami na świat i życie”. Kilka słów w kwestii rozumu praktycznego - Kaniowski, Andrzej Maciej (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The fate of “practical philosophy” in Poland was largely influenced by the views of Kazimierz Twardowski. This one, who had great merits for Polish philosophy, disciple of F. Brentano, was, on the one hand, a great admirer of Immanuel Kant and, on the other hand, completely disavowed his concept of practical reason. The source of the admiration was that Kant deprived metaphysics (in its then and former understanding) of its right to have itself as a science, while he demanded that philosophical thinking should be moved to criticism. However, Twardowski seemed to completely overlook the fact that Kant’s criticism cannot be detached from – the other side of it – Kant’s transcendentalism. Admittedly, in a certain trend of the continuation of Kant’s transcendentalism in German philosophy, as well as by its Polish creative followers, there was a “dogmatic swing in the clouds”. However, this is not yet a sufficient reason to part with practical reason and agree with Twardowski, who claims that philosophy is not in charge of dealing with “views on the world and life”. Such views, among other things, on matters which have been dealt with by “practical reason” for centuries, have contributed to the creation of a gap in Polish philosophy of thinking about the possibility of dealing with matters connected with the view on the world and life within philosophy. Such thought, on the other hand, was carried out in German philosophy (as a result of Hegel’s transformation of “practical reason” into “objective spirit”, and the turn to “practice” – which means turning to work, social activity, or communication), as well as in American ragmatism (Charles Sanders Peirce). The theory of communicative rationality by Jürgen Habermas, which is also a response to the challenge of pluralism of world views, emerges from the combination of these two currents of philosophical reflection. Twardowski’s stance on the non-philosophical nature of dealing with “views on the world and life” contributed to the fact that Polish philosophical thought did not follow the path leading from Hegel, through Wilhelm von Humboldt, Charles Sanders Peirce, Hans-Georg Gadamer to Jürgen Habermas.